Distributional Effect of Sharia Pawn Products on The Increase of Pawnshop Company Assets and Economic Growth of Jawa Barat - Permana, Iwan; Srisusilawati, Popon; Silviany, Irma Yulita (KEUNIS, 2025)
This study aims to analyze the influence of the distribution of sharia pawn products on the increase in the assets of pawnshop companies and economic growth in West Java during the period 2016-2020. This research is based on the decline in West Java's economic growth by -2.07% in 2020, despite an increase in the number of pawn companies and Islamic pawnshop assets. The research method used is descriptive analysis with a quantitative approach, using secondary data from the annual report of PT. Pawnshops and the Central Statistics Agency (BPS) of West Java. Data analysis was carried out by simple linear regression using SPSS version 20. The results show that the distribution of sharia pawn products has a positive influence on the increase in the assets of pawnshop companies (correlation R=0.820), but does not have a significant impact on economic growth (correlation R=0.544). The products analyzed include rahn such as sharia gold pawns and hajj portion financing, as well as non-rahn products such as sharia business loans and vehicle installments. This finding has important implications for the development of the sharia Pawnshop strategy to increase its contribution to regional economic growth.